Analysis of heart rate variability in the measurement of the activity of the autonomic nervous system: technical note. - Brandão, Glauber Sá; Sampaio, Antônia Adonis Callou; Brandão, Glaudson Sá; Urbano, Jéssica Julioti; Fonsêca, Nina Teixeira; Apostólico, Nadua; Oliveira, Ezequiel Fernandes de; Perez, Eduardo de Araujo; Almeida, Rafael da Guia; Dias, Ismael Sousa; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The analysis of heart rate variability (HRV) has been used as a resource for the measurement of autonomic nervous system activity in different situations. This analysis is based on identifying the strength of bands of low and high frequencies of the spectral function of the RR intervals in heart rate. Studies have shown that the related high frequency band parasympathetic tone controls the resting state, while exercise is associated with sympathetic activation, linked to lower frequency bands. The autonomic nervous system plays an important role in mediating the cardiovascular responses induced by stress. Objective: To describe a technique for analysis of heart rate variability in the measurement of autonomic nervous system activity. Discussion: To perform HRV analysis the “Nerve-Express” uses an effective and transparent visual representation, known as rhythmography method which reflects the structure of HRV wave and acts as a “fingerprint” of autonomic regulatory mechanisms. The wave RR intervals are recorded sequentially forming a rhythmogram, namely a picture of curved wave-specific variability of RR intervals.